Press coverage of the Zimbabwe men's national football team and re-imagining the nation - Moyo, Melussi (Midlands State University, 2019)
Discourses framing football reflect dominant, possibly, contesting ‘truths’, which themselves are linked to power relations and struggles within a given society. This study analyses the framing of the Zimbabwe men’ national football team (popularly known as The Zimbabwe Warriors) in The Sunday Mail, The Patriot and the Daily News on Sunday from March 2015 to April 2016. The three newspapers were purposively selected for being weeklies with a national coverage. A comparative analysis of the three newspapers sought to bring out what the papers made salient, silent and selected when framing news about the Warriors. It was concerned with finding out the frames of reference, factors influencing such frames and the most likely implications of these frames on the imaginations on Zimbabwean national identity. The rationale was that framing has always been about certain power and ideological positions, hence this study will help in unveiling the forces pushing for such imaginations by the press. Literature reviewed in this research are scholarly debates that make contribution to the concepts of representation, nation, nationhood, national identity and sports. Theories that informed the research were nationalism, national identity and discourse, power and framing. The research assumed the qualitative paradigm and employed qualitative techniques in gathering, analysing and presentation of data. It applied the critical paradigm or cultural studies perspective approach. Findings of the research concluded that language was tactically employed in the framing of the Warriors and relating the team to the aspirations of the nation as a whole. The strategic use of language in the coverage of the warriors in the mentioned newspapers can be understood as aiding in the nation building project specifically in The Sunday Mail and The Patriot. The research established that the representation of the Zimbabwe’s men national football team can be understood within the context of nationalism and patriotism. These concepts reveal the relationship that exist between football and notions of nationhood and national identity